"Domesticating" the City: Family Practices in Public Space. (August 2016) - Mandich, Giuliana; Cuzzocrea, Valentina
The aim of this article is to rethink the analysis of urban life and the practices involving the use of urban space. To that end, we focus on the value that such practices have for social enquiry by employing the concept of domestication, which was originally elaborated by Silverstone in the field of media and technology scholarship. Specifically, the potential value of such usage is to embed practices that produce space in the complexity of the everyday culture of families, and to enable an analysis of urban space in its dual articulation in both public and private culture. A discussion of how the concept has been applied in a study of how parents in a small Italian city include urban space in the domestic sphere offers an empirical substratum to our argument.